DESCRIBING THE HEIGHT GROWTH OF CORN USING LOGISTIC AND GOMPERTZ MODEL - Wayan Surya Wardhani; Prawitra Kusumastuti (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2013)
This paper is about a critical study on corn (Zea mays) plant with a non linear approach, as it is slowly growth rate at the initial stage of the cycle, followed by a rapid growth stage to a critical point then the height growth rate began to decline, reaching to a stability phase. The purpose of this research is to develope such a model to fit the height growth of corn (Zea mays) plant given microbe combination of Ochrobactrum sp.and Bacillus megatirium treatment; besides, to compare the plant absolute growth rate model between plant with microbe and non microbe treatment . A simple sigmoid model is preffered as it is easier to interpret the parameters biologically. The result shows that Logistic model is better fit in describing the height growth compare to Gompertz model, as it yields coefficient of determination is more than 99%. This model shows that the maximum height growth rate happens in about 40 day after planting. Based on the model, it showed that the absolute growth rate tend to be bell-shaped and right-skewed for Logistic and Gompertz respectively.Keywords : corn, Gompertz, height, Logistic, microbe